2014
DOI: 10.1097/bsd.0b013e31825bfc8e
|View full text |Cite
|
Sign up to set email alerts
|

Result of Posterior Instrumentation Without Fusion in the Management of Thoracolumbar and Lumbar Unstable Burst Fracture

Abstract: In thoracolumbar and lumbar unstable burst fracture, performing posterior instrumentation without fusion and removing the instrument after bone union is achieved is considered a useful procedure for selected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 13 publications
0
39
0
Order By: Relevance
“…This is probably due to the fusion performed during anterior stabilization, while no fusion was performed during solely posterior stabilization. Previous studies reported conflicting outcomes after posterior implant removal, ranging from no [17,18] to significant loss of correction [6,31]. Different studies are hard to compare while different follow-up times and surgical techniques are used.…”
Section: Kyphosis and Correlationsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is probably due to the fusion performed during anterior stabilization, while no fusion was performed during solely posterior stabilization. Previous studies reported conflicting outcomes after posterior implant removal, ranging from no [17,18] to significant loss of correction [6,31]. Different studies are hard to compare while different follow-up times and surgical techniques are used.…”
Section: Kyphosis and Correlationsmentioning
confidence: 99%
“…Some described only small cohorts [2,4,16] or focused largely on removal of long-segment fixation [10]. Other studies focused on the posterior stabilization itself, but advocated routine removal of implants to regain mobility of the spine and minimize potential damage [4,18]. In the current literature there is no consensus whether implants should be removed routinely after fracture consolidation, or only in selected cases with pain or other implant related symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Th e 10 articles -out of 33 -that met the criteria and were included in the fi nal database, discuss the most frequently employed surgical treatment methods for the thoracal and lumbar fractures: posterior short segment fi xation [10][11][12][13][14][15], on one hand, and anterior approach only, as well as posterior-anterior approach [16][17][18][19], on the other.…”
Section: Methodsmentioning
confidence: 99%
“…39 In this setting, the stress concentrated at the pedicle screws leads to a high incidence of instrumentation failure (loosening, breakage), nonunion of the fracture, and progressive loss of the achieved kyphosis reduction. 9,26 Therefore, additional load-sharing through anterior column reconstruction should be added. 20 Many authors have advocated anterior approach using strut grafts or cages and plates to establish anterior vertebral support.…”
Section: Introductionmentioning
confidence: 99%